2021
DOI: 10.1038/s41598-020-79443-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving sewage sludge compost process and quality by carbon sources addition

Abstract: In present study, the effects of carbon sources on compost process and quality were evaluated in the lab-scale sewage sludge (SS) composting. The composting experiments were performed for 32 days in 5 L reactors. The results showed that carbon sources could change the nitrogen conversion and improve the compost quality. Especially, the readily degradable carbon source could promote organic matter degradation, improve nitrogen conversion process and accelerate compost maturation. The addition of glucose and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 43 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, samples were collected from the uninoculated compost and mycelia-filled compost, respectively. Before sample collection, the composts in the top, middle, and bottom layers of the reactor were fully mixed ( Meng et al, 2021 ). All the samples were divided into two parts: one part was stored at 4 °C for physicochemical analysis and the other was frozen at −80 °C for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, samples were collected from the uninoculated compost and mycelia-filled compost, respectively. Before sample collection, the composts in the top, middle, and bottom layers of the reactor were fully mixed ( Meng et al, 2021 ). All the samples were divided into two parts: one part was stored at 4 °C for physicochemical analysis and the other was frozen at −80 °C for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported on the benefits that CSS can have on soil physical, chemical, and biological properties [14][15][16]. In this way, composting is a sustainable solution for companies managing sludge from WTPs [17,18] The Brazilian government recently adopted Resolution No. 498/2020, which has established regulations concerning the use of sewage sludge in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the addition of carbon sources (e.g., glucose and sucrose) can be quickly used by microbes as energy and available substances to increase the activity of microbes and nutrients assimilation. These additional substrate supplies could promote OM degradation, improve N-conversion processes, and accelerate compost maturation ( Meng et al., 2021 ). Based on these roles, the addition of CyanoMS to compost can enhance both microbial activity and dehydrogenase enzyme activity, thereby assisting nutrients availability and maturation ( El-Gamal, 2011 ).…”
Section: Resultsmentioning
confidence: 99%